SAGD-VL Framework: A Framework for Serious Adventure Game Development in A Virtual Laboratory - Diny Syarifah Sany (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
A virtual laboratory is an instructional approach to facilitate learning on a scientific procedure or experimental procedure to motivate students to think critically and to improve problem-solving skills through virtual media. A serious adventure game is a game that has a serious purpose for example Education but with an adventure genre that allows the user to go on adventures and explore within the game. The merging of a virtual laboratory and a serious adventure game will contribute to the progress of the education field and motivate students in virtual practicum activities. But currently, there is no particular software development framework for developing a serious adventure game for a virtual laboratory. This study aims to produce a serious adventure game framework for a virtual laboratory called SAGD-VL (Serious Adventure Game Development for Virtual Laboratory). SAGD-VL is obtained from analysis of characteristics of virtual laboratory, adventure game, similar software, existing game development methods, and game mechanics mapping framework so that an appropriate development framework will obtain and improve student ability. SAGD-VL consists of pre-production, production, testing, and post-production, and each of these steps has specific components. The SAGD-VL framework was tested by building a game according to the proposed framework. The proposed game mechanics is also the result of testing players repeatedly to get optimal game mechanics. This test aims to see the effectiveness of the game produced with SAGD-VL on improving the player's abilities and determine the importance of specific components in game design. The game was tested on 128 high school students by dividing them into reading groups and playing groups and tested by doing pre-test and post-test. The results show that the game produced by the SAGD-VL framework indicates a better positive impact than learning by reading and obtains an increase in post-test results achieving 115.74%.